Early thermal experience has different effects on growth and muscle fibre recruitment in spring- and autumn-running Atlantic salmon populations - Johnston, I A; McLay, H A; Abercromby, M; Robins, D (2000)
The consequence of early thermal experience for subsequent growth patterns was investigated in Atlantic salmon (Salmo salar L,), Spring- and autumn-running salmon mere caught in upland (Baddoch) and lowland (Sheeoch) tributaries of the River Dee, Aberdeenshire, Scotland, respectively, on the final stages of their spawning migrations. The eggs were incubated at the simulated natural temperature regime of each stream, which was on average 2.8 degrees C lower for the Baddoch, The offspring, representing 11 families per population, were transferred at first feeding to constant environmental conditions (12-14 degrees C; 16h:8h light:dark photoperiod) and reared in replicate tanks, Salmon of both populations were longer and heavier at 6 and 12 weeks in fish initially reared under the cooler Baddoch regime, Length frequency distributions became bimodal after 18 weeks, and only the upper growth mode was studied, Modelling of length distributions at 40 weeks revealed significantly different patterns of muscle growth according to initial temperature regime, but only for the Sheeoch salmon. In fish of Sheeoch origin, significantly more white muscle fibres were recruited per mm(2) increase in myotomal cross-sectional area at Sheeoch than at Baddoch temperatures (P<0.01). After 40 weeks, the density of white fibres was 10.4% higher in fish initially reared at the Sheeoch (533+/-6 mm(-2)) than at the Baddoch (483+/-5 mm(-2)) thermal regimes (means +/- S.E.M., 16 fish per group; P<0.001). Muscle satellite cells were identified using an antibody to c-met, At 24 weeks, the density of muscle satellite cells was 29% higher in Sheeoch salmon reared to first feeding at the temperature of their natal stream than at cooler Baddoch temperatures (P<0.01). In contrast, the number and size distributions of white muscle fibres in the myotomes of Baddoch salmon were independent of early thermal experience.